Rancang Bangun Alat Pendeteksi Kebusukan Telur Menggunakan Metode Fuzzy Logic Berbasis Mikrokontroler Arduino Nano 328 - David Christover; Adhe Yusphie Panca T.S.; Jordan Ananda Purnomo; Muhammad Muttaqin Yusup (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2019)
Eggs are a source of protein for the people of Indonesia and are always the main choice in meeting daily food needs. This is because the processing is practical and the price tends to be relatively cheap when compared to other animal protein sources.Currently the need for national chicken eggs has reached 65%, dominated by broiler eggs. It is predicted that the need for eggs nationally will increase until 2021 by 4.87% with a consumption level of 4.18% per year. Even so, in the selection of quality eggs from producers, sellers and consumers it is still fairly conventional and not guaranteed whether the eggs are suitable for consumption or not, so a new method is needed that is more efficient and knows the characteristics of good egg quality.Based on this background, a practical tool that is easy to use for conventional traders is formed.This tool works by using BH1750 and MQ-2 sensors as parameters in determining rotten eggs which are then processed using Arduino-nano 328 microcontroller, then processing the data using fuzzy logic artificial intelligence based on parameters that have been compiled from the membership function of each parameter that has been obtained from sensor. This research was conducted by collecting information first, then conducting a survey to a location in the form of a traditional market to find eggs taken randomly by testing 3 egg samples.Based on the results of three tests on 3 egg samples taken randomly, it was found that egg 2 with a Ro value of 4.29 K.Ohm, 4.53 K.Ohm and 4.79 K.Ohm and had a value of light intensity of 10.00 lux and 5.00 lux are eggs that have the best quality compared to 2 other eggs. Keywords: Egg, Fuzzy Logic, Light